Whose Knowledge Counts? A Reflection on the Field Narratives of Indigenous Health Knowledge and Practices - Subedi , Bamdev (Dhaulagiri Journal of Sociology and Anthropology, 2022)
Today's world is increasingly recognizing the value of indigenous knowledge and expressing concern over its erosion. The protection of indigenous knowledge has been a global policy priority. This paper draws from a qualitative study conducted in a village setting in South-West Nepal and aims to reflect on the local narratives of the erosion of indigenous health knowledge and practices (IHKPs). Data were collected from healers, patients, and key informants using interview and observation methods and analyzed thematically. The findings are organized in five broad themes: (i) The context of socio-economic change, (ii) Existing health knowledge and practices, (iii) A decline in herbal literacy and home remedy, (iv) Market influence, increased healthcare options, and the shrinking role of traditional healers, and (v) Value perceptions of indigenous knowledge. Though IHKPs remain an inseparable part of community life, the field narratives strongly indicate a decline in home and community-based health practices and an intergenerational loss of herbal knowledge. Taking insight from the critical medical anthropological perspective, this paper discusses the micro-experience and macro-influence and argues for recognizing the health knowledge of indigenous communities. The recognition of knowledge should be a political and policy decision in protecting and promoting IHKPs.